Soybean (Glycine max L. Merr.) Sprouts Germinated under Red Light Irradiation Induce Disease Resistance against Bacterial Rotting Disease - Dhakal, Radhika (PLoS One, 2015)
Specific wavelengths of light can exert various physiological changes in plants, including effects on responses to disease incidence. To determine whether specific light wavelength had effects on rotting disease caused by Pseudomonas putida 229, soybean sprouts were germinated under a narrow range of wavelengths from light emitting diodes (LEDs), including red (650–660), far red (720–730) and blue (440–450 nm) or broad range of wavelength from daylight fluorescence bulbs. The controls were composed of soybean sprouts germinated in darkness. After germination under different conditions for 5 days, the soybean sprouts were inoculated with P. putida 229 and the disease incidence was observed for 5 days. The sprouts exposed to red light showed increased resistance against P. putida 229 relative to those grown under other conditions. Soybean sprouts germinated under red light accumulated high levels of salicylic acid (SA) accompanied with up-regulation of the biosynthetic gene ICS and the pathogenesis- related (PR) gene PR-1, indicating that the resistance was induced by the action of SA via de novo synthesis of SA in the soybean sprouts by red light irradiation. Taken together, these data suggest that only the narrow range of red light can induce disease resistance in soybean sprouts, regulated by the SA-dependent pathway via the de novo synthesis of SA and up-regulation of PR genes.